ANALISIS STRATEGI KONSUMEN TERHADAP PEMBELIAN KRUPUK RAMBAK AR-ROHMAH DI KEMLAGI MOJOKERTO - Nidya Rizkawati; Eny Rachmawati; Adil Abdillah; Khasbulloh Huda (Politeknik Negeri Ambon, 2023)
From the initial survey it was discovered that AR-Rohmah's rambak cracker turnover decreased due to regional executions during the Covid-19 pandemic. The problem studied is how the marketing strategy, product quality, consumer tastes, brand image and purchase intention, does it affect the intention to buy AR-Rohmah rambak crackers. The purpose of this study was to determine the effect of marketing strategy, product quality, consumer tastes and brand image on interest in buying AR-Rohmah rambak crackers in Betro Kemlagi Village, Mojokerto. The population in this study are consumers who buy, have bought or know about AR-Rohmah rambak crackers. The number of samples is 80 people. Research using multiple linear regression analysis. The results showed that marketing strategy, product quality, consumer tastes and brand image had a partial and simultaneous significant effect on buying interest on AR-Rohmah rambak crackers in Betro Kemlagi Village, Mojokerto. This can be seen from the test results which have a sig value of less than 0.05, with a regression sales result Y = 8.649 + 0.107X1 + 0.300X2 + 0.322X3 + 0.300X4. While the coefficient of determination has a value of 76.9% which indicates that it has a large influence value simultaneously.